Characterization of Food Waste from a Campus Canteen as Potential Feedstock for Biogas Production - Lieke Riadi; Yunus Fransiscus; Tuani L. Simangunsong; Farida Suhud (Journal of Engineering and Technological Sciences, 2020)
Food waste collected from the Ubaya canteen was characterized for its potential for use as anaerobic feedstock. It was collected for 3 weeks on a daily basis and treated with 2 different pretreatments, i.e. mechanic and mechanic-thermal. The result showed that the physical and chemical properties of the food waste in the 3-week time period of collecting were not significantly different for both pretreatments. The VS/TS ratio was around 96.4% to 97.076% and C/N was in the range of 17.295 to 17.813 for the mechanic and mechanic-thermal treatments. Four semi-batch mesophilic anaerobic digesters were used in this study, with 1.215 gVS/L fed once (R1) and twice daily (R3); 2.43 gVS/L fed once (R2) and twice daily (R4). The maximum methane yield was determined to be 64.61 mL/gVS in R1 after 5 days of incubation and 57.41 mL/gVS in R3 after 4 days of incubation. Systems R2 and R4 showed maximum methane yields of 43.15 mL/gVS and 19.1 mL/gVS respectively.